An air‐ and moisture‐stable zinc(II) carbene dithiolate dimer showing fast thermally activated delayed fluorescence and Dexter energy transfer catalysis - Mrózek, Ondřej; Mitra, Mousree; Hupp, Benjamin; Belyaev, Andrey; Lüdtke, Nora; Wagner, Dorothee; Wang, Cui; Wenger, Oliver S.; Marian, Christel M.; Steffen, Andreas (Technische Universität Dortmund, 2023)
A dimeric ZnII carbene complex featuring bridging and chelating benzene-1,2-dithiolate ligands is highly stable towards air and water. The donor-Zn-acceptor structure leads to visible light emission in the solid state, solution and polymer matrices with λmax between 577–657 nm and, for zinc(II) complexes, unusually high radiative rate constants for triplet exciton decay of up to kr=1.5×105 s−1 at room temperature. Variable temperature and DFT/MRCI studies show that a small energy gap between the 1/3LL/LMCT states of only 79 meV is responsible for efficient thermally activated delayed fluorescence (TADF). Time-resolved luminescence and transient absorption studies confirm the occurrence of long-lived, dominantly ligand-to-ligand charge transfer excited states in solution, allowing for application in Dexter energy transfer photocatalysis.
Chemistry - a European journal; 29(23)
Keywords: carbenes; luminescence; photocatalysis; TADF; zinc; 540